KONSTITUSIONALITAS HAK ANGKET DEWAN PERWAKILAN RAKYAT (DPR) TERHADAP KOMISI PEMBERANTASAN KORUPSI (KPK) - Ismail Aris; Irfan Amir; Septian Amrianto (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2019)
The development of the state institutional theory requires that it no longer seals every State institution only to depend on 3 (three) branches of power as the teaching of the new separation of power theory. On the other hand, the decision of the Constitutional Court and the Revision of the KPK Law are placed as executive institutions. So it is debated whether the KPK is a subject that can be rounded up, because it is an executive institution or the KPK cannot be made a subject of questionnaire rights because of its position as an independent agency agency? This study aims to determine and analyze the authority of the DPR's questionnaire rights to the KPK and the constitutionality of the DPR's Questionnaire Rights to the KPK Perspectives on the revision of the KPK Law and Comparison in Various Countries. This type of research is the type of normative legal research. The approach used is the legislation approach and comparative law (comparison approach), the philosophical approach to the law (philosophical approach).The results of the study showed that the constitutionality of the DPR questionnaire rights was based on the original intent of the questionnaire right norm in a comprehensive draft amendment to the Basic Law, the questionnaire right was only aimed at state institutions of the executive family. In addition, Constitutional Court Decision No. 36-40 / PUU-XV / 2017, which categorizes the Corruption Eradication Commission as a group of executive institutions is in conflict with other Constitutional Court decisions, namely Decision of the Constitutional Court Number 012-016-019 / PUU-IV / 2006, 19 / PUU-V / 2007, 37-39 / PUU-VIII / 2010. 5 / PUU-IX / 2011, places the KPK as an independent agency and is categorized as faste jurisprudence (permanent jurisprudence). In addition, theoretically, the teaching of the new theory of separation of power teaches that it is no longer appropriate to place State institutions based only on 3 (three) branches of power. While the constitutionality of the DPR's questionnaire rights to the KPK Perspective of the revision of the KPK Law and Comparison in Various Countries is based on the results of research by researchers that the KPK's position in various countries is independent or dependent. For example, in South Africa, Zimbabwe, Egypt and Thailand. Likewise with the subject of state institutions that can be researched, there are no countries that address the right of questionnaires to these independent institutions. For example, the United States of America, Philippines, South Africa, all of whom address the questioning right of inquiry only as an executive state institution.